The concomitant anxiety and depression in patients with epilepsy caused by low-grade brain tumors - Sungel Xie; Jiao Qiao; Guoming Luan; Chuandong Liang; Chunyue You; Mingxiang Xie; Shunwu Xiao (Scientific Reports)
Abstract The aim of the study was to evaluate the concomitant psychiatric disorders of anxiety and depression in patients with epilepsy caused by low-grade brain tumors (LBTs). We retrospectively reviewed the clinical data of patients who underwent preoperative neuropsychological evaluations of anxiety and depression and subsequent epilepsy surgery for LBTs. The univariate and multivariate analyses were conducted to analyze the risk factors of the occurrence of anxiety and depression. Of the 107 patients included in the study, 42 patients (39.3%) were female, and 28 patients (26.2%) were children. The median age at surgery was 22 years (interquartile range [IQR]: 17–27 years old), the median age of seizure onset was 12 years (IQR: 6–18 years old), and the median duration of epilepsy was 84 months (IQR: 42–180 months). In total, 21 patients (19.6%) had psychiatric disorders of anxiety, and 26 patients (24.3%) had psychiatric disorders of depression. Through univariate and multivariate analysis, discordant (vs. concordant) interictal electroencephalogram (EEG) findings were found to be related to the presence of anxiety (P = 0.035, odds ratio [OR] = 3.35). Discordant (vs. concordant) ictal EEG findings (P = 0.015, OR = 4.44) and temporal location of tumor (P = 0.015, OR = 13.52) were found to be associated with the presence of depression. Psychiatric disorders of anxiety and/or depression could frequently occur in patients with epilepsy caused by LBTs. Thus, early screening and mental intervention are necessary, especially for those with discordant or wider epileptic discharges and temporal invasion of tumors.